PERANCANGAN UMKM CENTER DI KABUPATEN KUBU RAYA - Amelia, Friska; Lestari, Lestari; Andi, Uray Fery (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
The Small and Medium-Sized Enterprises (SMEs) Center is a place that is the center of SMEs activity to develop SMEs products and services. Based on data from the Ministry of Cooperatives and SMEs in 2021, SMEs in Indonesia absorb 96.9% of the total workforce and provide 99.9% of jobs. However, SMEs have Human Resources (HR), production and marketing, financing and institutional problems. This is because there are no facilities that provide integrated assistance for SMEs players. This problem occurs systematically, so a solution is needed which is also carried out systematically, namely by providing SMEs Center facilities in Kubu Raya Regency. The aim of the design is to produce an SMEs Center design that can accommodate Kubu Raya Regency SMEs development activities while also reflecting the identity of Kubu Raya Regency in the design. The design method used is the glass box method using five design stages, namely: ideas, information, analysis, synthesis, evaluation and optimization. The result is a building design that prioritizes functionality as the main building concept. The functional aspect can be seen in the spatial functions that complement each other and are integrated into one area to systematically facilitate the needs of Kubu Raya Regency SMEs. The building accommodates training, mentoring and commercial functions as the main functions. These functions are supported by management, distribution and regulatory functions and are supported by educational functions and service functions.